A meta-analytic review of self-reported, clinician-rated, and performance-based motivation measures in schizophrenia: Are we measuring the same "stuff"?. (April 2018) - Luther, Lauren; Firmin, Ruth L.; Lysaker, Paul H.; Minor, Kyle S.; Salyers, Michelle P.
Abstract: An array of self-reported, clinician-rated, and performance-based measures has been used to assess motivation in schizophrenia; however, the convergent validity evidence for these motivation assessment methods is mixed. The current study is a series of meta-analyses that summarize the relationships between methods of motivation measurement in 45 studies of people with schizophrenia. The overall mean effect size between self-reported and clinician-rated motivation measures ( r  = 0.27, k  = 33) was significant, positive, and approaching medium in magnitude, and the overall effect size between performance-based and clinician-rated motivation measures ( r  = 0.21, k  = 11) was positive, significant, and small in magnitude. The overall mean effect size between self-reported and performance-based motivation measures was negligible and non-significant ( r  = −0.001, k  = 2), but this meta-analysis was underpowered. Findings suggest modest convergent validity between clinician-rated and both self-reported and performance-based motivation measures, but additional work is needed to clarify the convergent validity between self-reported and performance-based measures. Further, there is likely more variability than similarity in the underlying construct that is being assessed across the three methods, particularly between the performance-based and other motivation measurement types. These motivation assessment methods should not be used interchangeably, and measures should be more precisely described as the specific motivational construct or domain they are capturing. Highlights: An array of motivation measures has been used in schizophrenia research. However, the convergent validity of these assessment methods is mixed. These meta-analyses summarize the relationships between motivation measure types. Results suggest negligent to medium relationships between motivation measure types. These measures are assessing a small amount of a shared underlying construct.